Grazing incidence X-ray diffraction and atomic force microscopy analysis of BaBi2Ta2O9 thin films - Mastelaro, V. R.; Foschini, C. R.; Varela, José Arana [UNESP] (Elsevier B.V., 2002)
Thin films of BaBi2Ta2O9 (BBT) composition were prepared through the metal organic decomposition method. The crystallinity, phase formation, crystallite size and morphology of the thin films were measured as a function of the type of substrate, stoichiometry of solution and process variables such as thickness and temperature. The thin films were investigated by grazing incidence X-ray diffractometry and atomic force microscopy (AFM) techniques. For the sample without excess of bismuth, diffraction peaks other than that of the BBT phase were observed. A well crystallized BBT single phase was observed for films prepared from a solution with 10% excess of bismuth, deposited on Si/Pt substrate, with a thickness up to 150 nm and sintered at temperatures of 700 degreesC. The thin BBT phase films heat-treated at 600 degreesC presented a diffraction pattern characteristic of samples with lower degree of crystallinity whereas for the thin films heat-treated at 800 degreesC, we observed the presence of other phases than the BBT. For the thin film deposited on the Sin+ substrate, we observe that the peaks corresponding to the BBT phase are broader than that observed on the samples deposited on the Pt and Si/Pt substrates. No variation of average crystallite size was observed as the excess of Bi increased from 10 to 20%. AFM images for the samples showed that the increasing the amount of bismuth promotes grain growth. The average surface roughness measured was in the range of 16-22 nm showing that the bismuth amount had no or little effect on the roughness of films. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: BaBi2Ta2O9; thin films; X-ray grazing incidence; crystallization